Rumahku Madrasahku Berbasis Android - Afit Muhammad Lukman; Ayu Noor Aziella; Fahlepi Roma Doni (Evolusi : Jurnal Sains dan Manajemen, 2021)
Family is the first and most important center of education for children. In the family, a child receives the guidance and upbringing of a parent and family environment whose child spends time in daily life. To reach that goal, parents must bring in Islamic values to their children, the values of Islam given by parents in daily life must be accompanied by good practices and examples in the family. Technological developments are now highly qualified, excessive use of excessive resources to make parents smart and creative to introduce the positive benefits of using this tool for their children. To support the person's tasks, create education-based applications to keep children up-to-date with media tools anywhere, anytime. In addition, this application was created with the aim of offering a more attractive educational value to attract interest in children's learning. But with this app does not mean that parents can disable the responsibilities of their children, but parents still have to follow the activities of their child.